An approach to assess the potential of agroecosystems in providing environmental services - Turetta, Ana Paula Dias; Tonucci, Rafael; de Mattos, Luciano Mansor; Amaro, George; Balieiro, Fabiano de Carvalho; Prado, Rachel Bardy; de Souza, Henrique Antunes; de Oliveira, Aline Pacobahyba (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to present an approach to evaluate soil functions in agroecosystems and their impact on environmental services (ES). An approach with case studies was proposed to assess the relationship between the establishment and management of agroecosystems, in three Brazilian biomes (Atlantic Forest, Cerrado, and Caatinga), and their environmental services provision, considering the specificities of each area. A set of soil parameters that can be used as indicators to monitor changes in the agroecosystem was also proposed. The environmental services types most affected by the establishment and management of the agroecosystems were the supporting and provisioning services, showing the potential of agricultural management in providing multiple services, besides food, fiber, and energy. “No fire use” and “agricultural consortium” were the criteria for the establishment and management of agroecosystems with greater potential to increase environmental services provision, whereas biomass stock in soil and litter was the most appropriate soil parameter to be used as an indicator to monitor the impact of agroecosystems in environmental services provision.